Food Functionality Evaluation of Enzymatic Hydrolysates Prepared from Edible Sea Cucumber Body Walls - Safitri, Erwina; Owada, Mayu; H. Kuziel, Olivia; Mizuta, Shoshi; Nagai, Takeshi; Saito, Masataka (Department of Technology of Agricultural product (THP) Jambi University, 2026)
Bioactive peptides from marine organisms, particularly sea cucumbers, represent a promising source of functional compounds with potential health benefits. This study investigated the bioactivities of hydrolysates prepared from several sea cucumber species using five proteolytic enzymes: Alcalase, bromelain, trypsin, papain, and pepsin. The hydrolysates were analyzed for angiotensin-converting enzyme (ACE) inhibitory activity, dipeptidyl peptidase-IV (DPP-IV) inhibitory activity, antioxidant capacity, and molecular weight distribution. Among the samples, 24-h Alcalase hydrolysates of red giant and Kinko sea cucumbers exhibited the highest combined ACE and DPP-IV inhibitory activities. Antioxidant analysis revealed that low DPPH radical scavenging activity showed relatively high oxygen radical absorbance capacity (ORAC) values, indicating different mechanisms of antioxidant action. Ethanol fractionation effectively enhanced ACE and DPP-IV inhibition as well as antioxidant activity. Amino acid composition analysis indicated proteins consistent with type I collagen as the primary source. Enzyme kinetics showed competitive inhibition for ACE and mixed-type inhibition for DPP-IV. Simulated gastrointestinal digestion caused only minor reductions in activity, suggesting that sea cucumber-derived peptides retain their bioactivity under physiological conditions. These findings highlight the potential of sea cucumber hydrolysates as nutraceutical ingredients.